Determination of pearlite morphology in high-carbon hot rolled steel - Szala J.; Kuc D. (Archives of Metallurgy and Materials, 2017)
The article presents the results of tests of influence of the thermo-mechanical treatment parameters on the mechanical properties and microstructure of steel C70D for wire rod. The methodology of quantitative description of pearlite morphology in steels with the use of the method on which a new computer program “PILS” - Pearlite Inter-Lamellar Spacing is based was presented. In order to verify the method, some quantitative tests of microstructure in samples after physical simulation of heat-plastic treatment were conducted on a deformation dilatometer device with diverse cooling rate for steel C70D. The process of rolling was conducted in simulation in continuous finishing train arrangement. Elaborated program and conducted tests will be used during preparations of modified technologies of wire rod rolling to prepare products made of steel, the microstructure of which is characterised with smaller interlamellar spacing.